Natural Decomposition Approximation Solution for First Order Nonlinear Differential Equations - Patra, A.; T. Shone, T.; B. Mishra, B. (International Journal of Engineering and Technology, 2018)
In this research paper, we propose the Natural decomposition method (NDM) to solve nonlinear first order differential equations. We compare the results obtained by NDM with the exact solutions. This method is a combination of the natural transform method and adomian decomposition method. By showing the less error one can be concluded that the NDM is easy to use and efficient.Â Â